CONCEPŢIA EXCLUZIUNII SOCIALE: ARGUMENTE PENTRU NOI MODALITĂŢI DE ABORDARE A PROBLEMEI INEGALITĂŢII ŞI DEPRAVĂRII - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
In this article the author presents the concept of social exclusion, mentioning that each debate regarding the social exclusion involves different perspectives and approaches. Thus, social exclusion can be seen as an appeal for radical changes of society’s structure (for example, the unemployment shall not represent anymore a problem for the whole society, but only for those who do not have a professional training, people with disabilities and other specific groups). The same concept can be used in order to develop values of group solidarity (for example, such as in case of ethnic groups). Thus, there is a risk that the concept of social exclusion can be included in particular ideologies, and this can diminish the focus on the main problem of social exclusion and namely to underline the possibilities of action in the sense of declining the forms and the effects of social exclusion in such a way facilitating the social integration and cooperation, because more than ever the problem of exclusion of a platform of multiple actions.